Peran Guru PAI dalam Bimbingan dan Konseling terhadap Perkembangan Akhlak Siswa di SMA X Cimahi - Siti Mariyah Ulfah; Adang M. Tsaury (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Counseling Guidance is the process of providing assistance through counseling interviews (face to face) by an expert (called a counselor) to individuals who are experiencing problems (called counselees) leading to the resolution of problems faced by counselees. Moral is a trait that is embedded in the soul of every human being that gives rise to various kinds of actions clearly and easily, without the need for thought and consideration. The role of PAI teachers in the development of students' morals is very important in order to foster students to become students who have noble character and character. Along with the development of the times, the school has now begun to experience many changes ranging from student morals, religion, discipline, and to daily discipline. One of these objectives is to determine the planning of PAI teachers in the formation of students' morals at SMA X Cimahi. This study uses a qualitative approach using descriptive methods, the data obtained through two types, namely primary data and secondary data. In this study, data were collected through interviews, observation and documentation studies. The results of this study PAI teachers play an important role in fostering students to become students who have noble character and character by instilling honesty, disciplined behavior, self-confidence, caring, independent, persistent and responsible attitudes. Factors that influence the role of PAI teachers in providing moral guidance to students. Abstrak. Bimbingan Konseling adalah proses pemberian bantuan yang dilakukan melalui wawancara konseling (face to face) oleh seorang ahli (disebut konselor) kepada individu yang sedang mengalami masalah (disebut konseli) bermuara pada teratasinya masalah yang dihadapi konseli. Akhlak ialah suatu sifat yang tertanam dalam jiwa setiap manusia yang menimbulkan macam-macam perbuatan dengan secara gamblang dan mudah, tanpa memerlukan pemikiran dan pertimbangan. Peran guru PAI pada perkembangan ahklak siswa sangat berperan penting agar membina anak didik menjadi siswa yang berakhlak mulia dan berbudi pekerti. Seiring berkembangnya zaman, sekolah tersebut kini sudah mulai mengalami banyak perubahan mulai dari akhlak siswa, agama, tata tertib, dan terhadap kedisiplinan sehari-hari. Salah satu dari tujuann ini untuk mengetahui perencanaan guru PAI dalam pembentukan akhlak siswa di SMA X Cimahi, Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode deskriptif, data yang diperoleh melalui dua jenis yaitu data primer dan data sekunder. Dalam penelitian ini data yang dikumpulkan melalui wawancara, observasi dan studi dokumentasi. Hasil penelitian ini Guru PAI berperan penting dalam membina peserta didik menjadi siswa yang berakhlak mulia dan berbudi pekerti dengan menanankam sifat jujur, perilaku disiplin, rasa percaya diri, sikap peduli, mandiri, gigih dan tanggung jawab. Faktor yang mempengaruhi peran guru PAI memberikan bimbingan akhlak pada siswa